2022
DOI: 10.3390/antiox11050837
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Encephalopathy and Melatonin

Abstract: Hepatic encephalopathy (HE) is a severe metabolic syndrome linked with acute/chronic hepatic disorders. HE is also a pernicious neuropsychiatric complication associated with cognitive decline, coma, and death. Limited therapies are available to treat HE, which is formidable to oversee in the clinic. Thus, determining a novel therapeutic approach is essential. The pathogenesis of HE has not been well established. According to various scientific reports, neuropathological symptoms arise due to excessive accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 195 publications
0
1
0
Order By: Relevance
“…Moreover, MT has significant effects on apoptosis, angiogenesis, tumor inhibition, and anti-proliferation of various tumor cells [ 21 ]. Studies have shown that MT can cross the blood-brain barrier and is involved in various neuroprotective actions on the brain [ 22 ]. MT also alleviates the overactivation of microglia, reduces nerve damage, and play a neuroprotective role [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MT has significant effects on apoptosis, angiogenesis, tumor inhibition, and anti-proliferation of various tumor cells [ 21 ]. Studies have shown that MT can cross the blood-brain barrier and is involved in various neuroprotective actions on the brain [ 22 ]. MT also alleviates the overactivation of microglia, reduces nerve damage, and play a neuroprotective role [ 23 ].…”
Section: Introductionmentioning
confidence: 99%